O IMPACTO DE CORTINAS, MOBILIÁRIO E VENTILADORES NA QUALIDADE ACÚSTICA DE SALAS DE AULA - Ikeda, Cristina Yukari Kawakita; Vittorino, Fúlvio; Ono, Rosaria (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Through the impulse response technique, measurements were performed in 3 classrooms with similar volume but with variations of furniture and fans. For the Reverberation Time (RT) and the Early Decay Time (EDT), the mean of the room per octave band, the standard deviation and the just noticeable difference (JND) were calculated. It was verified that there is heterogeneity between the points measured in the rooms and that is perceptible to its users. Therefore, one should not design a classroom with only the mean value of the acoustic descriptor in mind, since its mean value can be in adherence to the standards and recommendations, but it fails to meet them if verified in specific points. In addition to the reverberation time, it is recommended that other acoustic descriptors should be also evaluated to make the assessment of the room more complete. Operating modes of the room, such as open or closed windows, open or closed curtains and fans turned on or off, end up modifying the acoustic environment and must be taken into account in the acoustic design of rooms in which acoustic quality is essential.